Faunal Distribution and Seasonal Bio-ecology of Naturally Infected Sand flies in a New Endemic Zoonotic Cutaneous Leishmaniasis Focus of Southern Iran - Kourosh Azizi; Hayedeh Parvinjahromi; Mohammad Djaefar Moemenbellah-Fard; Bahador Sarkari; Mohammad Reza Fakoorziba (Tehran University of Medical Sciences, 2016)
Background: Cutaneous leishmaniasis is a major health problem in Iran in spite of implementation of control program. This infectious disease caused morbidity in less than 27000 people in 2010. This study was set to determine some ecological aspects of sand flies in Fasa district, Fars Province, southern Iran during 2011-2012. Methods: A total of 4792 sand flies were captured by means of sticky paper and CDC miniature light traps in 10 selected villages from the beginning to the end of the active season, from which 1115 specimens were captured for abundance study and 3677 specimens captured for monitoring monthly activities in Fasa. After species identification, extracted DNA was processed for detection of Leishmania parasite infection in sand flies. Results: Twelve species (6 Phlebotomus, 6 Sergentomyia) were identified. The most common sand fly was P. papatasi (82.4%) which represented 86.6% of sand flies from indoors and 82.7% from outdoors. The monthly activity of the species extended from April to the end of November. There were two peaks in the density curve of this species, one in June and the second in September. Natural infection to L. major was detected in P. papatasi (25 out of 130 sand flies, 19.2%). Conclusion: Phlebotomus papatasi is considered as a main vector of zoonotic cutaneous leishmaniasis in Fasa, Fars Province, south of Iran.